1989
DOI: 10.1128/jb.171.2.996-1001.1989
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an ammonium or methylammonium ion transport mutant of Escherichia coli and complementation by the cloned gene

Abstract: During nitrogen-limited growth, Escherichia coli expresses a specific ammonium or methylammonium ion transport system (Amt). Strains carrying defects in Amt have been isolated following TnlO transposon mutagenesis. These mutants have <10% of the transport activity of the parental strain. Glutamate, glutamine, arginine, or high levels (20 mM) of ammonium will serve as the sole nitrogen source for growth of these strains, and glutamine synthetase is normally expressed and repressed by the nitrogen regulatory (Nt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 27 publications
1
51
1
Order By: Relevance
“…The B. subtilis nrgB gene is located downstream from the nrgA gene. In E. coli, a gene (amtA) involved in ammonium transport has been cloned and sequenced (Fabiny et al, 1991;Jayakumar et al, 1989). The AmtA protein has been predicted to be a cytoplasmic component of an ammonium-transport system (Fabiny et al, 1991) and is not homologous to the ORF cloned in this study.…”
Section: Glnk Can Activate the Adenylylation Of Gs In Vitromentioning
confidence: 92%
“…The B. subtilis nrgB gene is located downstream from the nrgA gene. In E. coli, a gene (amtA) involved in ammonium transport has been cloned and sequenced (Fabiny et al, 1991;Jayakumar et al, 1989). The AmtA protein has been predicted to be a cytoplasmic component of an ammonium-transport system (Fabiny et al, 1991) and is not homologous to the ORF cloned in this study.…”
Section: Glnk Can Activate the Adenylylation Of Gs In Vitromentioning
confidence: 92%
“…Studies with mutant strains, which have lost the ability to actively transport NH,+ (Amt-), support this argument. For example, Klebsiella pneumoniae (Amt-) can grow only when NH4+, as sole source of N, is > 2 mM (Kleiner 1985), and E. coli (Amt-) cannot grow on 100 PM NH4+, whereas the Amt+ strain can (Jayakumar et al 1989). Passive NH3 diffusion will be an important transport mechanism when its rate is greater than cellular N demand.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of Amt and GS increased when V. harveyi grew on 5 1 mM NH,+. It is likely that transcription of the genes for Amt and GS is being derepressed simultaneously (Jayakumar et al 1986). Our V. harveyi results suggest that low and high affinity pathways of NH,+ uptake are operating together when extracellular NH,+ is within the range of N 0. l-l mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-dependent uptake of ammonium under limiting nitrogen supply has been described for bacteria (1) and fungi (3,4). Genetic studies identified genes of ammonium transporters (Amts) and methylamine permeases (Meps) and permitted investigation of their activity and regulation (3,5). The most widely accepted view is that they are secondary transporters mediating the uptake of the ammonium cation (6)(7)(8).…”
mentioning
confidence: 99%